Universality of Oxime K203 for Reactivation of Nerve Agent-Inhibited AChE - Kuca, Kamil; Hrabinova, Martina; Jun, Daniel; Musilek, Kamil; Penhaker, Marek; Krejcar, Ondrej; Soukup, Ondrej (Medicinal chemistry (Shariqah (United Arab Emirates)), 2015)
Oxime K203 seems to be the most promising oxime in case of reactivation of tabun-inhibited acetylcholinesterase (AChE). Although it was originally developed for treatment of tabun intoxications, it is able to reactivate cholinesterases inhibited by other nerve agents. This study is aimed at the evaluation of its potency in vitro against other nerve agents. For this purpose, sarin, tabun, cyclosarin, soman, VX, Russian VX and DFP were selected as members of the nerve agent family to check its universality. At high concentrations (10(-3) M), oxime K203 reached promising reactivation activity. At low concentrations, relevant for human use (10(-5) M), promising reactivation potency was obtained only with tabun. In conclusion, oxime K203 reactivates other nerve agents-inhibited cholinesterases, however its broad-spectrum reactivation is limited at high, for human not attainable, concentrations only.
Keywords: nervová bojová látka; Cholinesterase Inhibitors; pyridinové sloučeniny; Nerve Agents; Rats; Acetylcholinesterase; zvířata; Humans; Cholinesterase Reactivators; Oximes; cholinesterasové inhibitory; acetylcholinesterasa; oximy; reaktivátory cholinesterasy; krysa rodu Rattus; lidé; Pyridinium Compounds; Animals